Zwischen Muezzin und Kathedrale. Der Traum vom Mittelmeer als Musik - Schroeter-Wittke, Harald (Praktische Theologie)

Alles ist Musik! – „Wir bräuchten da mal was.“ Zum 100. Geburtstag von Magdalene Schauss-Flake (1921-2008) - Schroeter-Wittke, Harald; Schmidt-Eggert, Friedemann (Posaunenchor. Magazin für Bläserinnen und Bläser)

Erzählte Modegeschichte – Interviews mit Zeitzeugen des Couturiers Werner Lauer. In: nmt 2020 – Mode und Textil - Haller, Melanie (Netzwerk Mode und Textil, 2021 (Peer Reviewed))

Iron oxide catalysts for CO oxidation : from basic structure-activity-correlation to an advanced preparation strategy for highly active catalysts - Schlicher, Steffen

Der Weg zur Gewalt – Ein zwischenzuständliches Gespräch über Dumpfbacken, Depressionen und Druckwellen. - Jacke, Christoph (Kaput - Magazin für Insolvenz & Pop)

COVID-19 Reporting and Willingness to Pay for Leisure Activities - Ortmann, Regina; Warkulat, Sonja; Krull, Sebastian; Klocke, Nina; Pelster, Matthias

Real effects of an international tax reform for MNEs - Ortmann, Regina; Simons, Dirk; Voeller, Dennis

Optical Arbitrary Waveform Measurement Using Silicon Photonic Slicing Filters - Fang, Dengyang; Zazzi, Andrea; Müller, Juliana; Dray, Daniel; Fullner, Christoph; Marin-Palomo, Pablo; Tabatabaei Mashayekh, Alireza; Dipta Das, Arka; Weizel, Maxim; Gudyriev, Sergiy; Freude, Wolfgang; Randel, Sebastian; et al. (Journal of Lightwave Technology)
We demonstrate an optical arbitrary waveform measurement (OAWM) system that exploits a bank of silicon photonic (SiP) frequency-tunable coupled-resonator optical waveguide (CROW) filters for gapless spectral slicing of broadband optical signals. The spectral slices are coherently detected using a frequency comb as a multi-wavelength local oscillator (LO) and stitched together by digital signal processing (DSP). For high-quality signal reconstruction, we have implemented a maximum-ratio combining (MRC) technique based on precise calibration of the complex-valued opto-electronic transfer functions of all detection paths. In a proof-of-concept experiment, we demonstrate the viability of the scheme by implementing a four-channel system that offers an overall detection bandwidth of 140 GHz. Exploiting a femtosecond laser with precisely known pulse shape for calibration along with dynamic amplitude and phase estimation, we reconstruct 100 GBd QPSK, 16QAM and 64QAM optical data signals. The reconstructed signals show improved quality compared to that obtained with a single high-speed intradyne receiver, while the electronic bandwidth requirements of the individual coherent receivers are greatly reduced.
Keywords: Atomic and Molecular Physics; and Optics

Optically Enabled ADCs and Application to Optical Communications - Zazzi, Andrea; Müller, Juliana; Weizel, Maxim; Koch, Jonas; Fang, Dengyang; Moscoso-Martir, Alvaro; Tabatabaei Mashayekh, Ali; Das, Arka D.; Drays, Daniel; Merget, Florian; Kartner, Franz X.; Pachnicke, Stephan; et al. (IEEE Open Journal of the Solid-State Circuits Society)
Electrical-optical signal processing has been shown to be a promising path to overcome the limitations of state-of-the-art all-electrical data converters. In addition to ultra-broadband signal processing, it allows leveraging ultra-low jitter mode-locked lasers and thus increasing the aperture jitter limited effective number of bits at high analog signal frequencies. In this paper, we review our recent progress towards optically enabled time- and frequency-interleaved analog-to-digital converters, as well as their monolithic integration in electronic-photonic integrated circuits. For signal frequencies up to 65 GHz, an optoelectronic track-and-hold amplifier based on the source-emitter-follower architecture is shown as a power efficient approach in optically enabled BiCMOS technology. At higher signal frequencies, integrated photonic filters enable signal slicing in the frequency domain and further scaling of the conversion bandwidth, with the reconstruction of a 140 GHz optical signal being shown. We further show how such optically enabled data converter architectures can be applied to a nonlinear Fourier transform based integrated transceiver in particular and discuss their applicability to broadband optical links in general.

Sprachwissenschaft und Fremdsprachendidaktik: Konstruktionen und Konstruktionslernen.

Confinement Effects for Efficient Macrocyclization Reactions with Supported Cationic Molybdenum Imido Alkylidene N-Heterocyclic Carbene Complexes - Ziegler, Felix; Kraus, Hamzeh; Benedikter, Mathis J.; Wang, Dongren; Bruckner, Johanna R.; Nowakowski, Michal; Weißer, Kilian; Solodenko, Helena; Schmitz, Guido; Bauer, Matthias; Hansen, Niels; Buchmeiser, Michael R. (ACS Catalysis)
Keywords: Catalysis; General Chemistry

Fundamental Characterization, Photophysics and Photocatalysis of a Base Metal Iron(II)‐Cobalt(III) Dyad - Huber‐Gedert, Marina; Nowakowski, Michał; Kertmen, Ahmet; Burkhardt, Lukas; Lindner, Natalia; Schoch, Roland; Herbst‐Irmer, Regine; Neuba, Adam; Schmitz, Lennart; Choi, Tae‐Kyu; Kubicki, Jacek; Gawelda, Wojciech; et al. (Chemistry – A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Rh(I)/(III)‐N‐Heterocyclic Carbene Complexes: Effect of Steric Confinement Upon Immobilization on Regio‐ and Stereoselectivity in the Hydrosilylation of Alkynes - Panyam, Pradeep K. R.; Atwi, Boshra; Ziegler, Felix; Frey, Wolfgang; Nowakowski, Michal; Bauer, Matthias; Buchmeiser, Michael R. (Chemistry – A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Immobilized Platinum Hydride Species as Catalysts for Olefin Isomerizations and Enyne Cycloisomerizations - Maier, Sarah; Cronin, Steve P.; Vu Dinh, Manh-Anh; Li, Zheng; Dyballa, Michael; Nowakowski, Michal; Bauer, Matthias; Estes, Deven P. (Organometallics)
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry

Ni-Based Electrocatalysts for Unconventional CO2 Reduction Reaction to Formic Acid - Albero, Josep; Lepre, Enrico; Heske, Julian; Nowakowski, Michal; Scoppola, Ernesto; Zizak, Ivo Zizak; Heil, Tobias Heil; D. Kühne, Thomas; Antonietti, Markus; López-Salas, Nieves (Proceedings of the International Conference on Frontiers in Electrocatalytic Transformations)

A fully cross-diffusive two-component evolution system: Existence and qualitative analysis via entropy-consistent thin-film-type approximation. - Tao, Youshan; Winkler, Michael (Journal of Functional Analysis)

The dampening role of large repulsive convection in a chemotaxis system modeling tumor angiogenesis. - Tao, Youshan; Winkler, Michael (Nonlinear Analysis, Theory, Methods and Applications)

Immediate regularization of measure-type population densities in a two-dimensional chemotaxis system with signal consumption. - Wang, Yulan; Winkler, Michael; Xiang, Zhaoyin (Science China Mathematics)

Small-density solutiions in Keller-Segel systems involving rapidly decaying diffusivities. - Ding, Mengyao; Winkler, Michael (Nonlinear Differential Equatiions and Applicatiions)

Global smooth solutions in a two-dimensional cross-diffusion system modeling propagation of urban crime. - Tao, Youshan; Winkler, Michael (Communications in Mathematical Sciences)

Taxis-driven formation of singular hotspots in a May-Nowak type model for virus infection. - Tao, Youshan; Winkler, Michael (SIAM Journal on Mathematical Analysis)

Local energy estimates and global solvability in a threee-dimensional chemotaxis-fluid system with prescribed signal on the boundary. - Wang, Yulan; Winkler, Michael; Xiang, Zhaoyin (Communications in Partial Differential Equations)

Global solvability in a threee-dimensional Keller-Segel.Stokes system involving arbitrary superlinear logistic degradation - Wang, Yulan; Winkler, Michael; Xiang, Zhaoyin (Advances in Nonlinear Analysis)

Critical mass for infinite-time blow-up in a haptotaxis system with nonlinear zero-order interaction - Tao, Youshan; Winkler, Michael (Discrete and Continuous Dynamical Systems)

„Vom Fahr-Zeug zum Fahr-Ding. Ein Heideggerianischer Kommentar zum autonomen Automobil“ - Alpsancar, Suzana (Autonome Autos – Die Zukunft des Verkehrs und die Dispositive der Mobilität)

Building, emptying out, or dreaming? Action structures and space in students’ metaphors of academic writing - Scharlau, Ingrid; Karsten, A.; Rohlfing, Katharina J. (Journal of Writing Research)
Keywords: Literature and Literary Theory; Linguistics and Language; Language and Linguistics; Education

Comparing the Effects of a Different Social Partner (Social Robot vs. Human) on Children's Social Referencing in Interaction - Tolksdorf, Nils Frederik; Crawshaw, Camilla E.; Rohlfing, Katharina J. (Frontiers in Education)
Social robots have emerged as a new digital technology that is increasingly being implemented in the educational landscape. While social robots could be deployed to assist young children with their learning in a variety of different ways, the typical approach in educational practices is to supplement the learning process rather than to replace the human caregiver, e.g., the teacher, parent, educator or therapist. When functioning in the role of an educational assistant, social robots will likely constitute a part of a triadic interaction with the child and the human caregiver. Surprisingly, there is little research that systematically investigates the role of the caregiver by examining the ways in which children involve or check in with them during their interaction with another partner — a phenomenon that is known as social referencing. In the present study, we investigated social referencing in the context of a dyadic child–robot interaction. Over the course of four sessions within our longitudinal language-learning study, we observed how 20 pre-school children aged 4–5 years checked in with their accompanying caregivers who were not actively involved in the language-learning procedure. The children participating in the study were randomly assigned to either an interaction with a social robot or a human partner. Our results revealed that all children across both conditions utilized social referencing behaviors to address their caregiver. However, we found that the children who interacted with the social robot did so significantly more frequently in each of the four sessions than those who interacted with the human partner. Further analyses showed that no significant change in their behavior over the course of the sessions could be observed. Findings are discussed with regard to the caregiver's role during children's interactions with social robots and the implications for future interaction design.

Do Shy Children Keep more Distance from a Social Robot? Exploring Shy Children’s Proxemics with a Social Robot or a Human - Tolksdorf, Nils Frederik; Viertel, Fanziska E.; Crawshaw, Camilla E.; Rohlfing, Katharina J. (Interaction Design and Children)

Nonlinear waveguides for integrated quantum light source - Domeneguetti, Renato R.; Conradi, Hauke; Kleinert, Moritz; Kießler, Christian; Stefszky, Michael; Herrmann, Harald; Silberhorn, Christine; Andersen, Ulrik L.; Neergaard-Nielsen, Jonas Schou; Gehring, Tobias (2021 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference)
We experimentally investigate the generation of continuous-wave optical squeezing from a titanium-indiffused lithium niobate waveguide resonator at low and high frequencies. The device promises integration with different platform chips for more complex optical systems.
Keywords: Optical systems; Polymer waveguides; Quantum key distribution; Quantum light sources; Squeezed states; Waveguides

Lehrerkooperation und Digitalisierung - Gestaltung digital-kooperativer Arbeitsbeziehungen von Lehrkräften und ReferendarInnen am Beispiel des Schulfachs Pädagogik - Engemann, M.; Herzig, Bardo (Fachliche Bildung und digitale Transformation - Fachdidaktische Forschung und Diskurse. Fachtagung der Gesellschaft für Fachdidaktik 2020)

Prospektive und prozessbezogene Kompetenzanalyse - Gestaltung und Erprobung eines Vorgehens - Depenbusch, Sarah; Bender, Elena; Schaper, Niclas

Investigating the multidimensionality of informal learning: Validation of a short measure for white‐collar workers - Decius, Julian; Knappstein, Michael; Schaper, Niclas; Seifert, Andreas (Human Resource Development Quarterly)
Keywords: Organizational Behavior and Human Resource Management; Arts and Humanities (miscellaneous)

The Hen-Egg-Problem of Informal Workplace Learning & Work Design: The Mediating Role of Job Crafting. - Decius, Julian; Schaper, Niclas; Seifert, Andreas (Academy of Management Prodeedings)

Seismograf Pop - Jacke, Christoph; Roenneke, Stefanie; Göymen, Cigdem (Pop-Musik*)

Multimode integrated SU(1,1) interferometer - Ferreri, A.; Santandrea, Matteo; Stefszky, Michael; Luo, Kai Hong; Herrmann, Harald; Silberhorn, Christine; Sharapova, Polina (Conference on Lasers and Electro-Optics)
We present a frequency multimode integrated SU (1,1) interferometer with a polarization converter and strong signal-idler photon correlations. Phase sensitivity below the shot noise limit is demonstrated, various filtering and seeding strategies are discussed.

Sachunterricht lehren in Zeiten der Pandemie – Eine Online-Befragung zu den Auswirkungen der digitalen Lehre auf den Materialeinsatz und die Selbstwirksamkeitserwartungen von Lehrenden in der Sachunterrichtsdidaktik an drei deutschen Hochschulstandorten. Posterpräsentation auf der 30. Jahrestagung der Gesellschaft für Didaktik des Sachunterrichts (GDSU) an der Universität Paderborn (aufgrund des pandemiebedingten digitalen Tagungsformats entfallen) - Thonemann, Lisa; Reh, Anne; Deutschen, Katrin; Lakemeyer, Jana Marie; Blumberg, Eva

Digitales Sachunterrichtsstudium in der Corona-Krise – Eine empirische Evaluationsstudie zur Rezeption des analogen und webbasierten Unterstützungsangebots des Paderborner Lernzentrums „Sachunterrichtstreff“ bei Sachunterrichtsstudierenden im Grund- und Förderschullehramt. Posterpräsentation auf der 30. Jahrestagung der Gesellschaft für Didaktik des Sachunterrichts (GDSU) an der Universität Paderborn (aufgrund des pandemiebedingten digitalen Tagungsformats entfallen) - Deppe, Franziska; Reh, Anne; Blumberg, Eva

Voraussetzungen bei Sachunterrichtsstudierenden zum Herausforderungsbereich Digitalisierung in Schule und Hochschule – Eine empirische Online-Befragung bei Lehramtsstudierenden an Grundschulen und für sonderpädagogische Förderung. Posterpräsentation auf der 30. Jahrestagung der Gesellschaft für Didaktik des Sachunterrichts (GDSU) an der Universität Paderborn (aufgrund des pandemiebedingten digitalen Tagungsformats entfallen) - Brenke, Laurien; Blumberg, Eva

Einsatz digitaler Medien im Sachunterricht – Die Coronakrise als Spiegel für die fehlende Digitalisierung im deutschen Bildungswesen? Was können wir von Schweden lernen? Vortrag auf der 30. Jahrestagung der Gesellschaft für Didaktik des Sachunterrichts (GDSU) an der Universität Paderborn (aufgrund des pandemiebedingten digitalen Tagungsformats entfallen) - Sicking, Annika; Blumberg, Eva

Digital gestütztes Lernen im naturwissenschaftlichen Sachunterricht? Eine kriteriengeleitete Analyse digitaler sachunterrichtsbezogener Lernangebote. Posterpräsentation auf der 30. Jahrestagung der Gesellschaft für Didaktik des Sachunterrichts (GDSU) an der Universität Paderborn (aufgrund des pandemiebedingten digitalen Tagungsformats entfallen) - Stump, Martin; Blumberg, Eva

Prozessmodell Generative Unterrichtsplanung Sachunterricht (GUS). Posterpräsentation auf der 30. Jahrestagung der Gesellschaft für Didaktik des Sachunterrichts (GDSU) an der Universität Paderborn (aufgrund des pandemiebedingten digitalen Tagungsformats entfallen) - Tänzer, Sandra; Lauterbach, Roland; Blumberg, Eva; Grittner, Frauke; Lange, Jochen; Schomaker, Claudia

transMINT4.0 – Grenzen überwinden, MINT-Bildung verbinden durch außerschulische Lernorte und den Einsatz digitaler Medien. Eingeladener digital synchroner Vortrag in der MINT-Aktionswoche von MINTvernetzt - Blumberg, Eva; Schulze, Jan Roland; Temmen, Katrin; Schäfers, Johannes

Preisabsprachen in der Automobilindustrie - eine wettbewerbspolitische Analyse - Yigitbas , Osman

Facebooks digitale Währung - eine wettbewerbspolitische Analyse - Schulte, Marcel

Faszination 3D-Film: Entwicklung einer 3D-Konstruktion - Hüsing, Sven; Weiser, Niklas; Biehler, Rolf (mathematik lehren)

Der Beruf Grundschullehrer*in: Zukunftsfragen. Podcast im Rahmen der Reihe „Zukunftsgespräche“ der Peter Gläsel Stiftung - Büker, Petra
März 2021 https://pg-stiftung.net/zukunftsgespraeche/

Children as (Co)Researchers as an Opportunity to influence School Life: A Didactic Approach and its Relevance in the Perspective of Children. Beitrag im Rahmen des Symposiums: Participation to Connect Members of the School Community an der ECER (European Conference on Educational Research), University of Geneva. Online - Büker, Petra; Hüpping, Birgit
September 2021

Partizipation als Veränderung. Eine Aufforderung an Grundschule und Forschung - Büker, Petra; Hüpping, Birgit; Zala-Mezö, Enikö (Zeitschrift für Grundschulforschung)

Simulation of Guided Waves in Cylinders Subject to Arbitrary Boundary Conditions Using the Scaled Boundary Finite Element Method - Itner, D.; Gravenkamp, H.; Dreiling, Dmitrij; Feldmann, Nadine; Henning, Bernd (14th WCCM-ECCOMAS Congress)

CxNy: New Carbon Nitride Organic Photocatalysts - Lopez Salas, Nieves; Albero, Josep (Frontiers in Materials)
The search for metal-free and visible light-responsive materials for photocatalytic applications has attracted the interest of not only academics but also the industry in the last decades. Since graphitic carbon nitride (g-C 3 N 4 ) was first reported as a metal-free photocatalyst, this has been widely investigated in different light-driven reactions. However, the high recombination rate, low electrical conductivity, and lack of photoresponse in most of the visible range have elicited the search for alternatives. In this regard, a broad family of carbon nitride (C x N y ) materials was anticipated several decades ago. However, the attention of the researchers in these materials has just been awakened in the last years due to the recent success in the syntheses of some of these materials (i.e., C 3 N 3 , C 2 N, C 3 N, and C 3 N 5 , among others), together with theoretical simulations pointing at the excellent physico-chemical properties (i.e., crystalline structure and chemical morphology, electronic configuration and semiconducting nature, or high refractive index and hardness, among others) and optoelectronic applications of these materials. The performance of C x N y , beyond C 3 N 4 , has been barely evaluated in real applications, including energy conversion, storage, and adsorption technologies, and further work must be carried out, especially experimentally, in order to confirm the high expectations raised by simulations and theoretical calculations. Herein, we have summarized the scarce literature related to recent results reporting the synthetic routes, structures, and performance of these materials as photocatalysts. Moreover, the challenges and perspectives at the forefront of this field using C x N y materials are disclosed. We aim to stimulate the research of this new generation of C x N y -based photocatalysts, beyond C 3 N 4 , with improved photocatalytic efficiencies by harnessing the striking structural, electronic, and optical properties of this new family of materials.
Keywords: Materials Science (miscellaneous)